Pelatihan Pembuatan Pelet Apung pada UMKM Kelompok Budidaya Ikan Omah Jala - Arif Rakhman Suharso; Anang Budhi Nugroho; Ario Hendartono; Wahyu Ari Putranto; Hero Budi Santoso; Akhmad Nuriyanis (Lembaga Pengembangan Kinerja Dosen, 2026)
The extruder-type floating pellet machine is a form of appropriate technology that works by using a screw system to push the raw material while applying pressure to form dense pellets. The main source of raw material for making these pellets comes from trash fish, which are small fish caught by fishermen that are unfit for consumption and have low economic value. Trash fish are relatively cheap because they are classified as non-economical, but they have great potential for use as fish feed. Their distinctive strong aroma can stimulate fish appetite, while their relatively high protein content makes them an ideal source of nutrition. Before use, the trash fish are first dried and then ground using a flour machine to achieve a fine texture. The floured material is then mixed and the moisture content is adjusted to around 42%, so that the extrusion process can run optimally when using the extruder-type pellet machine. The material formulation consists of 70% trash fish meal, 15% corn meal, and 15% wheat flour. The resulting pellets are then tested in a feed laboratory and show protein levels ranging from 30-40%, depending on the quality of the trash fish raw material used. This community service activity involves fish farmer groups in the Beji area, East Ungaran District, which is expected to increase fish farmer insight on how to make floating pellets using an extruder type pellet printing machine.